Food choices [videorecording (DVD)] (Gravitas Ventures, 2016)
This film takes a broader look and explores the impact that our food choices have not only on our own health, but also on the health of our planet as well as on the lives of other living species on earth and shows how everything is intrinsically interconnected. This film features interviews with renowned doctors, nutritionists, environmental experts, holistic health practitioners, athletes, musicians, celebrities, authors, bloggers as well as people that shared their amazing stories.